2016 IEEE International Conference on High Voltage Engineering and Application (ICHVE) 2016
DOI: 10.1109/ichve.2016.7800894
|View full text |Cite
|
Sign up to set email alerts
|

Inception and breakdown voltages of insulating liquids under DC stress

Abstract: Abstract-This paper investigated the streamer inception and breakdown properties of a mineral oil and a synthetic ester liquid under DC stress up to 100 kV. To observe the effect of tip radius on streamer inception, the point-plane electrodes configuration with a fixed gap distance of 10 mm and point electrode with the radii of 5 µm, 10 µm, 20 µm and 50 µm were used. To observe the effect of gap distance on breakdown voltage, a point-to-plane electrode configuration with a fixed tip radius of 10 µm and variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Xiang et al [21] have studied the inception and breakdown characteristics of insulating liquids under DC stress. They have indicated that intensity of light and number of pulses that have occurred on occurrence of discharges is high under positive polarity.…”
Section: Variation In Pdiv Of Thermally Aged Ester Oilmentioning
confidence: 99%
“…Xiang et al [21] have studied the inception and breakdown characteristics of insulating liquids under DC stress. They have indicated that intensity of light and number of pulses that have occurred on occurrence of discharges is high under positive polarity.…”
Section: Variation In Pdiv Of Thermally Aged Ester Oilmentioning
confidence: 99%
“…The increase in the charge density and ionic mobility of fluid at higher temperatures could be responsible for the increase in the streaming current [40]. On comparing these results with the conventional mineral oil, the charging tendency of mineral oil is very low due to inherent aromatic suppressants [33]. Also, these higher charging current observed in punga oil could be reduced by adding optimum amount of benzotriazole (BTA) additive which has been illustrated in our previous studies [40].…”
Section: E Electrostatic Charging Tendency (Ect) Of Punga Oilmentioning
confidence: 52%
“…It is observed that compared to breakdown strength under positive DC and AC voltages, the electrode gap's breakdown strength is higher under negative DC voltage. Under DC voltage, the space charge injected at the needle tip weakens the boundary electric field reducing the streamer propagation [33]. But the alternating waveform involved in AC supply voltage causes ionization of charges at the needle tip during the positive half cycle and in the negative half cycle, the charges formed tries to reduce the gap spacing [11] between the needle tip and ground thereby initiating discharges to occur at a lower voltage compared to its impact under DC voltages.…”
Section: Variation In Breakdown Voltage Of Punga Oil With Magnetic Fieldmentioning
confidence: 99%